Self-Potential Method to Assess Embankment Stability: A Study related to the Sidoarjo Mud Flow - Sungkono Sungkono; Masithoh N. Wasilah; Yekti Widyaningrum; Wildan M. Hidayatullah; Fandi A. Fathoni; Alwi Husein (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
The stability of an embankment is generally influenced by a number of factors, such as deformation, fractures, overtopping, seepage, etc. Fractures and seepage are commonly found in the LUSI (Sidoarjo mud flow) embankment. In this study, analysis of self-potential (SP) data was applied to identify fractures and seepage in the LUSI embankment. Noise-Assisted Multivariate Empirical Mode Decomposition (NA-MEMD) and Continuous Wavelet Transform (CWT) were applied to determine the location of seepage and fractures in the subsurface based on SP data. The results were correlated with the 2D direct current resistivity (DCR) method, which showed that both methods worked well and were compatible in detecting and localizing fracture and seepage in the LUSI embankment.